2013
DOI: 10.1111/j.1758-5740.2012.00214.x
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Chronic Anterior Sternoclavicular Joint Dislocations Using a Palmaris Longus Autograft

Abstract: Background Sternoclavicular joint (SCJ) injuries are uncommon. A minority of patients with anterior dislocation progress to chronic instability associated with pain and a limitation of activities, and thus surgery should be considered. A retrospective case series of an all anterior reconstruction of the SCJ with autologous palmaris longus is presented. Methods Five consecutive patients underwent SCJ stabilization using a palmaris longus autograft tunnelled through the anterior cortices of the medial clavicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…When there is a lateral compressive force effect on the shoulder girdle, it can cause rupture of the anterior capsule and part of the costoclavicular ligament, which results in the anterior dislocation of the sternoclavicular joint. Due to the broken ligaments with a high energy injury, redislocation happens frequently after manual reduction, and the conservative treatment shows poor efficacy in sternoclavicular joint dislocation patients, for instance with progressive pain limiting the movement of the shoulder girdle and decreasing quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…When there is a lateral compressive force effect on the shoulder girdle, it can cause rupture of the anterior capsule and part of the costoclavicular ligament, which results in the anterior dislocation of the sternoclavicular joint. Due to the broken ligaments with a high energy injury, redislocation happens frequently after manual reduction, and the conservative treatment shows poor efficacy in sternoclavicular joint dislocation patients, for instance with progressive pain limiting the movement of the shoulder girdle and decreasing quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…14 Various techniques have been proposed for the surgical management of the unstable symptomatic SCJ. These include fixation with Kirschner wires (k-wires) 15 or sutures, 4 ligament reconstruction using sternocleidomastoid transfer 16 or palmaris longus 17,18 and gracilis 8 tendon autografts, fiber-wire, 6 tight-rope 19 or stabilization by fixation to the first rib. 20 Although relatively satisfactory results have been reported, K-wires carry a significant risk to mediastinal structures with migration, which can result in fatal great vessel perforation and are, therefore, currently out of favour.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been reported that closed reduction can be the final therapeutic regimen for 38% of patients with such lesions, 13 conservative treatment shows poor efficacy in patients with sternoclavicular joint dislocation; these patients develop progressive pain of the sternoclavicular joint, limiting the movement of the affected shoulder girdle and decreasing their quality of life. 4 While there are other reported surgical treatments including Kirschner wire or plate fixation, medial clavicle resection, costoclavicular ligament reconstruction, 3-point anchor suture, and sternoclavicular joint reconstruction with the palmaris longus or allograft tendon, [4][5][6][7] in all these surgeries, either the amphiarthrodial function of the sternoclavicular joint is sacrificed to achieve firm fixation, or postoperative complications such as internal fixation displacement, reduction loss, and infections are usually observed because of the complex surgical manipulation. Thus far, there has been no well-recognized internal fixation equipment suitable for all sternoclavicular dislocation and medial clavicle fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Conservative treatments include manipulative reduction and limb immobilization; however, maintaining position after fracture dislocation is difficult, and long-term immobilization could severely affect the quality of life of the patient. Surgical treatments include Kirschner wire fixation, plate fixation, ligament reconstruction around the sternoclavicular joint, and medial clavicle resection; [4][5][6][7] thus far, no standardized surgical pattern or internal fixation device has been developed. Several surgical approaches carry a risk of multiple complications.…”
Section: Introductionmentioning
confidence: 99%